Characterization of Radial ZnO-Core/ZnS-Shell Nanowire Heterostructures ALD-Deposited at Atmospheric Pressure Using DEZn, N2O and DTBS. (8th November 2016) - Wen, Sheng-Wen; Huang, Bo-Hao; Kang, Jun-Jie; Lin, Tai-Yuan; Hsu, Hsun-Feng; Ni, Ho-Ching; Hou, Ching-Hsiang; Lai, Hui Ting; Gong, Jyh-Rong
Abstract : In this study, radial ZnO-core/ZnS-shell nanowire heterostructures were deposited at atmospheric pressure by atomic layer deposition (ALD) using diethylzinc (DEZn), nitrous oxide (N2 O) and ditert-butylsulfide (DTBS) precursors. The structural and optical properties of radial ZnO-core/ZnS-shell nanowire heterostructures were characterized using θ-2θX-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM), scanning electron microscopy (SEM), and photoluminescence spectroscopy (PL). It was found that both ZnO-core and ZnS-shell of the ALD-deposited radial ZnO-core/ZnS-shell nanowire heterostructure were wurtzite in nature based upon the results of HRTEM investigations. Moiré fringes were identified in the radial ZnO-core/ZnS-shell nanowire structure with an observed period being in good agreement with the lattice mismatch between ZnO-core and ZnS-shell of the pseudomorphic ZnO-core/ZnS-shell nanowire heterostructure. Neutral donor excitonic emissions (D°X) along with related longitudinal optical phonon (LO) replicas of ZnO cores were observed in the 10 K PL of the ALD-deposited radial ZnO-core/ZnS-shell nanowire heterostructures.